Kategismusprediking in die Nederduitsch Hervormde Kerk van Afrika - Dreyer, T. F. J. (Hervormde teologiese studies, 1992)
Doctrinal preaching in the Nederduitsch Hervormde Kerk van Afrika The churches that sprung from the Reformation in the sixteenth century, had firmly established, by the turn of the century, doctrinal teaching as an important part of church life. There was to be doctrinal teaching during the Sunday afternoon service. This frequent preaching, however, deteriorated with time. This paper tries to re-establish the original purpose and function of doctrinal preaching, and evaluate its use for modern times. Finally the paper attempts to point out the significance of doctrinal teaching and how to implement it within the church today.